2017
DOI: 10.1080/02656736.2017.1396364
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional area of the murine aorta linearly increases with increasing core body temperature

Abstract: Previously unidentified increases in aortic area due to increasing core temperature are biologically important because they may affect conductive and convective heat transfer. Leveraging non-invasive methodology to quantify sex and age dependent vascular responses due to increasing core temperature could be combined with bioheat modelling in order to improve understanding of thermoregulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
19
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(26 citation statements)
references
References 60 publications
6
19
1
Order By: Relevance
“…Additionally, the relative reduction in area at the infrarenal aorta was greater in young animals. This suggests that mature male mice may be exhibiting deleterious effects based on both sex and age, which is consistent with previously published results from mice and humans …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Additionally, the relative reduction in area at the infrarenal aorta was greater in young animals. This suggests that mature male mice may be exhibiting deleterious effects based on both sex and age, which is consistent with previously published results from mice and humans …”
Section: Discussionsupporting
confidence: 93%
“…Thus, on average, the vessel is left in an enlarged state and the resulting reduction in strain values demonstrates we are beginning to disrupt the vessel's ability to deform during the cardiac cycle in the same manner as young counterparts. Although other studies have not addressed the relationship between changes in strain and area directly, murine and human data demonstrate a similar relationship between larger area and reduced strain that we observe with dobutamine. Geometric changes have long been a foci with respect to aortic disease .…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Male mice were chosen in this initial study of artery–vein pairs because this sex showed the smallest response in the aorta in our previous work (male: 0.019 mm 2 /°C vs. female: 0.024 mm 2 /°C, (Crouch et al. )). Mice were anesthetized with 1.25–2% isoflurane in 1 L/min of oxygen (Constantinides et al.…”
Section: Methodsmentioning
confidence: 99%
“…Previous work in the lab quantified cardiac output and the arterial response (area and cyclic strain) to increases in core temperature from head‐to‐toe (Crouch et al. ). However, data regarding changes in the core (alternatively, deep) veins are still missing from this body of work.…”
Section: Introductionmentioning
confidence: 99%